Zoning Regulations that Promote Local Generation of Energy, Water and Food Resources, With Recommendations for the City of Boston. - Pantalone, Stephen. (2017)
Abstract: This research explores the effect of U.S. regulatory land use policy on localizing energy, water and food resource generation in efforts to address environmental sustainability. This thesis presents the consequences of not tackling environmental sustainability identified in scientific reports and articles. Research from books, reports, articles and best practice guides are used to analyze the potential for localizing resource generation through new technologies and alternative practices, and to identify obstacles they face in regulatory land use policy. The research shows that many of the new technologies and alternative practices that would localize resources are generally not encouraged in local zoning regulations. However, several cities across the U.S. are taking steps to remove these obstacles. This thesis applies these concepts and issues to the City of Boston's zoning code, and specifically the neighborhood districts of Dorchester, the South End, and Roslindale. Based on these findings, this thesis recommends changes to the Boston zoning code that would promote local generation of energy, water and food resources.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Jon Witten.; Committee: Ann Rappaport.; Keywords: Land Use Planning, and Sustainability.